2022
DOI: 10.37358/mp.22.1.5573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fracture Resistance of PEEK and Fibre Posts of the Endodontically Treated Teeth

Abstract: This in vitro study aimed to compare the fracture resistance between pressed custom-made polyetheretherketone (PEEK) post and core and fibre reinforced post and composite core. A total of 40 single rooted extracted teeth were selected, endodontically treated, and prepared to receive the posts. Specimens were randomly divided into two main groups (n=20/group): group 1, (PEEK); group 2, fibre post. PEEK post was manufactured with a computer-aided design/computer-aided manufacturing system further divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
2
Order By: Relevance
“…In a study reporting similar results, the fracture resistance values of glass fiber and PEEK posts were compared. According to the study results, the fracture resistance of PEEK posts was found to be statistically higher [34]. Unlike the findings of our study, some studies report that the fracture resistance of PEEK posts is significantly lower compared to glass fiber posts [35].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In a study reporting similar results, the fracture resistance values of glass fiber and PEEK posts were compared. According to the study results, the fracture resistance of PEEK posts was found to be statistically higher [34]. Unlike the findings of our study, some studies report that the fracture resistance of PEEK posts is significantly lower compared to glass fiber posts [35].…”
Section: Discussioncontrasting
confidence: 86%
“…Whereas there is a consensus in the literature that the fracture resistance of PEEK posts is lower compared to metal posts under conditions without the ferrule effect, studies on the fracture resistance of PEEK and glass fiber posts report different results [34]. According to the findings of our research, there is no significant difference in terms of fracture resistance between the glass fiber and PEEK post groups without ferrule preparation.…”
Section: Discussioncontrasting
confidence: 67%
“…In the present study, the exclusion of crown fabrication aimed to amplify the effect of post and core materials in the assessment of fracture resistance of endodontically treated teeth. [41][42][43][44] On the other hand, studies [40,60,61] that used a crown or coping to cover post and core restorations had fracture resistance higher than the current study, however, this might conceal the actual differences between the used custom made post and core materials. Thermal and mechanical aging have signi cant impacts on the bonding and fracture resistance of endodontically treated teeth restored with post and core restorations.…”
Section: Discussionmentioning
confidence: 77%
“…[62,63]. Moreover, several studies [9,30,42,47,55,64] refrained from conducting arti cial aging, emphasizing that their investigations were speci cally focused on the materials and methodology rather than projecting outcomes under different conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation